The Role of Context in Understanding Pragmatic Meaning - Rhaudhotul Fadhilah; Miftahul Jannah; Dwita Lestari; Dinda Sundana; Deasy Yunita (Universitas Negeri Medan, 2024)
This paper investigates the importance of context in understanding pragmatic meanings. Adopting a literature review approach with an interpretive framework, the study collects data by examining the works of scholars to uncover various perspectives on context. The analysis process involves identifying key theories, organizing the findings, interpreting the outcomes, and composing the journal article. The research identifies 11 key aspects of context that influence the interpretation of pragmatic meanings. The findings highlight the fundamental difference between semantic and pragmatic meaning, emphasizing that pragmatic meaning is always shaped by context. Therefore, it concludes that pragmatic meaning is heavily dependent on extra-lingual factors. Keywords: context, interpretive approach, extra-lingual factors, pragmatic meaning.